Environmental Sustainability and Its Impact on Brand Loyalty of Vietnamese in Vietnam and Australia - Ho, Bich; Marinova, Dora (Research Papers, 2023)
Brand loyalty is a significant goal and motivation for retailers, particularly for countries with emerging economies, such as Vietnam. The paper presents the results from a study conducted in 2020 (prior to the COVID-19 pandemic) which uses structural equation modelling and is based on an online survey of 578 people with a Vietnamese background, 296 residing in Vietnam and 282 in Australia. This study shows that there is a link between environmental sustainability and brand loyalty; however, it is influenced by the cultural differences between Vietnam and Australia. No link between ecological performance and brand satisfaction was identified. The study offers an insight to retailers that if they are to improve their environmental performance, this would result in higher customer loyalty.
Keywords: Brand; Vietnam; Sustainability; Loyalty; Australia; Retail; Enviromental